Analisis Pesan Komunikasi Islam dalam Lirik Lagu Ruang Rindu dan Permintaan Hati Karya Band Letto : (Studi Analisis Semiotika Charles Sanders Peirce) - Siti Rohmah; Alifa Nur Fitri (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This research aims to analyze the Islamic Communication Message in the Lyrics of Ruang Rindu and the Letto Band's Heart Request using Charles Sanders Peirce's semiotic approach. The author uses qualitative descriptive research to describe research data. Data was taken using the documentation technique for the lyrics of the song Letto Ruang Rindu and Hati's request. The results of this research show that the lyrics of this song have a deep Islamic communication message. The lyrics describe the search for meaning in life, feelings of loss, and hope for certainty in spiritual relationships. The meaning of the lyrics of the song Ruang Rindu describes the longing and search for deep meaning in a spiritual relationship with God. This song reflects a person's journey in finding calm and closeness to the Creator amidst doubt and silence. The message in this song invites listeners to reflect on their relationship with God and find peace by adhering to spiritual values.